Clinical effects of morning and afternoon radiotherapy on high-grade gliomas. (4th May 2021) - Sapienza, Lucas Gomes; Nasra, Karim; Berry, Ryan; Danesh, Leana; Little, Tania; Abu-Isa, Eyad
ABSTRACT: Initial clinical reports comparing the delivery of radiotherapy (RT) at distinct times of the day suggest that this strategy might affect toxicity and oncologic outcomes of radiation for multiple human tissues, but the clinical effects on high-grade gliomas (HGG) are unknown. The present study addresses the hypothesis that radiotherapy treatment time of the day (RT-TTD) influences outcome and/or toxic events in HGG. Patients treated between 2009–2018 were reviewed (n = 109). Outcomes were local control (LC), distant CNS control (DCNSC), progression-free survival (PFS), and overall survival (OS). RT-TTD was classified as morning if ≥50% of fractions were delivered before 12:00 h (n = 70) or as afternoon (n = 39) if after 12:00 h. The average age was 62.6 years (range: 14.5–86.9) and 80% were glioblastoma. The median follow-up was 10.9 months (range: 0.4–57.2). The 1y/3y LC, DCNSC, and PFS were: 61.3%/28.1%, 86.8%/65.2%, and 39.7%/10.2%, respectively. Equivalent PFS was found between morning and afternoon groups (HR 1.27; p = .3). The median OS was 16.5 months. Patients treated in the afternoon had worse survival in the univariate analysis (HR 1.72; p = .05), not confirmed after multivariate analysis (HR 0.92, p = .76). Patients with worse baseline performance status and treatment interruptions showed worse PFS and OS. The proportion of patients that developed grade 3 acute toxicity, pseudo progression, and definitive treatment interruptions were 10.1%, 9.2%, and 7.3%, respectively, and were not affected by RT-TTD. In conclusion, for patients with HGG, there was no difference in PFS and OS between patients treated in the morning or afternoon. Of note, definitive treatment interruptions adversely affected outcomes and should be avoided, especially in patients with low performance status. Based on these clinical findings, high-grade glioma cells may not be the best initial model to be irradiated in order to study the effects of chronotherapy.